Who owns religion?: scholars and their publics in the late twentieth century - Patton, Laurie L. (The University of Chicago Press, 2019)
Part One. Scandals, Publics, and the Recent Study of Religion -- Scandalous Controversy and Public Spaces -- Public Spheres/Public Spaces -- The 1990s: Cultural Recognition, Internet Utopias, and Postcolonial Identities -- Ancestors' Publics -- Part Two. Case Studies -- Mother Earth: The Near Impossibility of a Public -- The Construction of Religious Boundaries: Competing Public Histories -- Songs of Wisdom and Circles of Dance: An Emerging Global Public -- The Illegitimacy of Jesus: Strong Publics in Conflict -- God's Phallus: The Refusal of Public Engagement -- K¿lī's Child: The Challenge of Secret Publics -- Part Three. New Publics, New Possibilities -- Scholars, Foolish Wisdom, and Dwelling in the Space Between